Hispanic Immigrants' Vulnerabilities to Flood and Hurricane Hazards in Two United States Metropolitan Areas - Maldonado, Alejandra; Collins, Timothy W.; Grineski, Sara E. (Geographical Review, 2016)
INTRODUCTION A substantial body of research has focused on the vulnerability of racial/ethnic minorities to hazards and disasters. This work has lumped people with diverse characteristics into general groups, such as "Hispanic" or "Latino/a" (Bolin 2007). Today, Hispanic immigrants represent an important group in U.S. society due to their large and increasing population. According to American Community Survey estimates, as of 2013 there were 21 million foreign-born Hispanics in the U.S., representing 52.5 percent of the total foreign-born population and 6 percent of the U.S. population. Hispanic immigrants are distinguishable from U.S.–born Hispanics due to their concerns about immigration status as well as cultural and linguistic differences. Treating Hispanics as a homogenous group may mask important differences between foreign-born and U.S.–born Hispanics and lead to erroneous conclusions about their disaster vulnerabilities. In order to address the particular risks experienced by foreign-born Hispanics in the U.S., more research characterizing salient dimensions of their vulnerability to hazards and disasters is needed. This study highlights particular vulnerabilities of foreign-born Hispanics living at risk to flooding and hurricanes in the Houston, Texas, and Miami, Florida, Metropolitan Statistical Areas (MSAs) by examining their self-protective actions, and their perceptions of and knowledge about flood risks, in comparison to both U.S.–born non-Hispanic whites and U.S.–born Hispanics. It addresses two research questions: what differences exist in self-protective actions and perceptions of risk between Hispanic immigrants, U.S.–born Hispanics, and U.S.–born white residents who live at high risk to flooding and hurricanes; and why do differences in self-protective actions and perceptions of risk exist between Hispanic immigrants, U.S.–born Hispanics, and U.S.–born white residents who live at high risk to flooding and hurricanes? Approaching these questions, we analyze primary structured survey and semistructured interview data using a mixed-method analysis approach, which enables us to clarify particular factors that place Hispanic immigrants at increased risk to flood and hurricane disasters. LITERATURE REVIEW The last three decades have marked the emergence of a social-vulnerability perspective on hazards and disasters, which emphasizes the influence of inequalities on differential risks (Hewitt 1983, 1997; Peacock and others 1997; Wisner and others 2004; Tierney 2006; Thomas and others 2013). From this perspective, risk is determined partly by human exposure to a hazard and partly by people's social vulnerability. While there is debate about the meaning and measurement of social vulnerability, the following definition is useful: "the characteristics of a person or group and their situation that influence their capacity to anticipate, cope with, resist and recover from the impact of a natural hazard" (Wisner and others 2004, 11). In this study, we analyze the social vulnerability of Hispanic immigrants in terms of self-protection from flood/hurricane hazards, and perceptions of and knowledge about flood/hurricane risks. Here, self-protection is defined as any structural or nonstructural strategy used by households to minimize loss and enable recovery from the impacts of flood or hurricane hazard exposures (NRC 2006). Self-protection strategies in the context of flood and hurricane hazards include home structural as well as nonstructural actions. Structural mitigation actions include elevating home structures, flood-proofing homes, and installing hurricane shutters (FEMA 2014). They also include nonstructural actions, such as maintaining flood insurance. In terms of nonstructural self-protection strategies, in the U.S., flood insurance plays an important protective role, since it provides compensation for property losses. Disaster preparedness is another dimension of nonstructural self-protection that has been examined extensively (Mulilis and Lippa 1990; Faupel and others 1992; Norris and others 1999; Sattler and others 2000; Miceli and others 2008; Borque and others 2013), and can include evacuation planning, maintaining basic supplies (for example, a first aid kit) and being alert (for example, being attentive to hazard reports). …
MAG ID: 1945348152

Exploring the Environmental Justice Implications of Hurricane Harvey Flooding in Greater Houston, Texas. - Chakraborty, Jayajit; Collins, Timothy W.; Grineski, Sara E. (American Journal of Public Health, 2019)
Objectives. To assess the environmental justice implications of flooding from Hurricane Harvey in Greater Houston, Texas, we analyzed whether the areal extent of flooding was distributed inequitably with respect to race, ethnicity, and socioeconomic status, after controlling for relevant explanatory factors.Methods. Our study integrated cartographic information from Harvey’s Inundation Footprint, developed by the US Federal Emergency Management Agency, with sociodemographic data from the 2012–2016 American Community Survey. Statistical analyses were based on bivariate correlations and multivariate generalized estimating equations.Results. The areal extent of Harvey-induced flooding was significantly greater in neighborhoods with a higher proportion of non-Hispanic Black and socioeconomically deprived residents after we controlled for contextual factors and clustering.Conclusions. Results provide evidence of racial/ethnic and socioeconomic injustices in the distribution of flooding and represent an importa...
MAG ID: 2906468836

Exposure to flood hazards in Miami and Houston: are Hispanic immigrants at greater risk than other social groups? - Maldonado, Alejandra; Collins, Timothy W.; Grineski, Sara E.; Chakraborty, Jayajit (International Journal of Environmental Research and Public Health, 2016)
Although numerous studies have been conducted on the vulnerability of marginalized groups in the environmental justice (EJ) and hazards fields, analysts have tended to lump people together in broad racial/ethnic categories without regard for substantial within-group heterogeneity. This paper addresses that limitation by examining whether Hispanic immigrants are disproportionately exposed to risks from flood hazards relative to other racial/ethnic groups (including US-born Hispanics), adjusting for relevant covariates. Survey data were collected for 1283 adult householders in the Houston and Miami Metropolitan Statistical Areas (MSAs) and flood risk was estimated using their residential presence/absence within federally-designated 100-year flood zones. Generalized estimating equations (GEE) with binary logistic specifications that adjust for county-level clustering were used to analyze (separately) and compare the Houston (N = 546) and Miami (N = 560) MSAs in order to clarify determinants of household exposure to flood risk. GEE results in Houston indicate that Hispanic immigrants have the greatest likelihood, and non-Hispanic Whites the least likelihood, of residing in a 100-year flood zone. Miami GEE results contrastingly reveal that non-Hispanic Whites have a significantly greater likelihood of residing in a flood zone when compared to Hispanic immigrants. These divergent results suggest that human-flood hazard relationships have been structured differently between the two MSAs, possibly due to the contrasting role that water-based amenities have played in urbanization within the two study areas. Future EJ research and practice should differentiate between Hispanic subgroups based on nativity status and attend to contextual factors influencing environmental risk disparities.
MAG ID: 2480285246

Social and spatial inequities in exposure to flood risk in Miami, Florida - Chakraborty, Jayajit; Collins, Timothy W.; Montgomery, Marilyn; Grineski, Sara E. (Natural Hazards Review, 2014)
AbstractAlthough environmental justice (EJ) research in the United States has traditionally focused on technological hazards such as air pollution or hazardous waste, the adverse and unequal impacts of Hurricane Katrina have prompted researchers to examine the EJ implications of natural events such as hurricanes and floods. This paper contributes to this emerging literature on EJ and social vulnerability to natural hazards by analyzing racial/ethnic and socioeconomic inequities in the distribution of flood risk exposure in the Miami Metropolitan Statistical Area (MSA), Florida—one of the most hurricane-prone areas in the world and one of the most ethnically and socioeconomically diverse MSAs in the United States. Although previous studies have relied exclusively on the 100-year floodplain to assess the spatial extent of flood exposure, this study makes a systematic distinction between different types of flood zones on the basis of both the probability (100-year versus 500-year versus low/no risk) of flood...
MAG ID: 1991854274